PENGARUH MEREK DAN LOKASI TERHADAP KEPUTUSAN KONSUMEN BELANJA DI PASAR SWALAYAN MAJU BERSAMA MMTC MEDAN - AJI PRABOWO; TOGU HARLEN LBN. RAJA; MUHAMMAD SYAFRIL (JURNAL ILMIAH SIMANTEK, 2021)
This study was conducted to find out the Brand and Location of Consumer Decisions, this study uses quantitative methodswith associative approaches. In this study, the consumer population who shopped at self-service advanced with MMTCMedan. How to take samples in this study using probability sampling techniques using the accindental sampling method asmany as 96 respondents. Data analysis techniques use validity tests, reliability tests, classical assumption tests, multiplelinear regression analysis, t tests, F tests and coefficients of determination (R2) using spss version 20 applications.The result of the t variable t test of the Brand t calculated 5,509 > t table of 1,986 means that the brand affects consumerdecisions and the location variable t calculates by 1,693 < t the table of 1,986 means that location has very little influence onconsumer decisions. Test F brand variable and location F calculated by 27,992 > F table 3.09 shows that brands andlocations together influence consumer decisions.